GAMBARAN PEMANFAATAN PELAYANAN KESEHATAN DI INSTALASI RAWAT INAP RUMAH SAKIT TK.II PELAMONIA KOTA MAKASSAR - Hilla Lasya; Rika Kurnia Kandacong, Sherly Rudianti Batter (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The utilization of health services tightly to do with when someone require the health service and how far the effectiveness of the service. The research aims to know a picture of the utilization health of hospitalization installs at the hospital TK.II Pelamonia Makassar City. This type of research is quantitative with the design of deskriptif. The population in research is all the patients common that had been using and while the health service. Withdrawal of samples using purposive sampling with a large sample of 67 patients common. The data analysis done is univariate. The research result obtained the perception petients about the hospital TK.II Pelamonia known 67 patients common (100%) said that the system of health services hospital TK.II Pelamonia this good. While the facility hospital as much 56 patients common (83,6%) said available. Then access geographical (distance) as much 48 patients common (71,6%) said easy reach and the health workers who said the act of health workers quite conscientious 57 patients common (85,1%). The conclusions from this research is the utilization of health services in installs the hospitalizations got perception positive as well the facility supportive so that the hospital TK.II Pelamonia got success in the utilization of the health service